STRATEGY INCREASING FOREIGN INVESTMENT IN MEDAN CITY - Nana Gustiana; Isfenti Sadalia; Sukaria Sinulingga (CV. Radja Publika, 2023)
Weak economic growth and low foreign investment coming into Medan City from 2018-2022 are the basis for selecting an effective strategy to be implemented in Medan City. This study aims to identify and analyze the factors and formulate an effective strategy for increasing foreign investment in the city of Medan. The method used in this study is the SWOT analysis method (Strength, Weakness, Opportunity, and Threats) and AHP (Analytical Hierarchy Process) analysis. The results of the research analysis show that there are several strategies for increasing foreign investment in Medan City, namely: First, increasing the upstream-downstream industry partnership integration scheme in Medan City (0.415). Second, the preparation of regional incentive facility policies through the establishment of regional regulations (0.321). Third, developing green investment (green investment) in the city of Medan (0.136). Fourth, increasing information technology-based innovation to support potential leading sectors (0.128).